Cytotoxic assay of endophytic fungus 1.2.11 secondary metabolites from Brucea javanica (L) Merr towards cancer cell in vitro (Medical Journal of Indonesia, 2006)
Cytotoxic assay of secondary metabolite endophytic fungus 1.2.11 from Brucea javanica (L) Merr has been carried out. Brucea javanica fruit collected from Cianjur was used in this experiment. Cytotoxic assay was done on Raji, NS-1, HeLa and Vero cells. The observation was done for 24 hours and also for 48 hours. IC50 was calculated using the Rich and Muench theory. To observe the working mechanism of cytotoxic process, DNA staining with etidium bromide and acridine orange was conducted. The cytotoxic assay of endophytic fungi 1.2.11 showed an IC50 of 58.35 Î¼g/ml, 88.39 Î¼g/ml on Raji cell,; 162.09 Î¼g/ml, 66.24 Î¼g/ml on NS cell; 361.21 Î¼g/ml, 219.97 Î¼g/ml on HeLa cell; and lastly 1075.18 Î¼g/ml, 656.82 Î¼g/ml on Vero cell after 24 and 48 hour incubation respectively. The results of this study showed that secondary metabolite of endophytic fungus 1.2.11 has selective cytotoxic effect towards cancer cell and also showed that it might cause apoptosis in NS-1cell. (Med J Indones 2006; 15:137-44) Keywords: Brucea javanica (L.) Merr, endophytic microbe, Cytotoxic assay, endophytic isolate 1.2.11, apoptosis